2013
DOI: 10.5455/jbh.20130921013627
|View full text |Cite
|
Sign up to set email alerts
|

Receptivity and preferences in cancer risk reduction lifestyle programs: A survey of colorectal cancer family members

Abstract: Background Cancer is a shared family experience, and thus the purpose of this study was to assess receptivity and preferences for cancer risk reduction programs among at-risk family members with two or more relatives affected with colorectal cancer (CRC). Methods The sample comprised 401 at-risk family members with two or more relatives affected with CRC from the Colon Cancer Family Registry. In March 2009, respondents completed a mailed survey assessing receptivity and preferences for participating in cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…The majority (85%) of the participants endorsed interest in cancer risk-reduction programs. Similar to previous research [ 23 , 24 , 28 , 29 , 31 , 43 , 44 ], these results emphasized that unaffected family members had a desire to improve and/or make health behavior changes to reduce their cancer risk. Moreover, our study participants expressed the most interest in weight management and nutritional programs – which are related and shown in the literature to be linked to reducing cancer risk [ 8 , 13 , 14 , 45 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The majority (85%) of the participants endorsed interest in cancer risk-reduction programs. Similar to previous research [ 23 , 24 , 28 , 29 , 31 , 43 , 44 ], these results emphasized that unaffected family members had a desire to improve and/or make health behavior changes to reduce their cancer risk. Moreover, our study participants expressed the most interest in weight management and nutritional programs – which are related and shown in the literature to be linked to reducing cancer risk [ 8 , 13 , 14 , 45 ].…”
Section: Discussionsupporting
confidence: 88%
“…This heightened awareness, coupled with the fact that cancer risk reducing and promoting behaviors run in families [ 22 ], suggests that families with a diagnosis of cancer in a member present logical target for cancer risk reduction interventions. In prior research [ 23 , 24 ], unaffected family members of those with a family history of colon and pancreatic cancer expressed interest in making lifestyle changes in nutrition and weight management to reduce their risk of cancer. Many of these family members preferred to participate in programs with their family or friends, rather than alone.…”
Section: Introductionmentioning
confidence: 99%
“…It showed that 81% of 401 persons with two or more relatives diagnosed with colorectal cancer were willing to take part in a lifestyle programme and there was a significant correlation between a higher level of concern about cancer and an inclination to participate in these programmes. 20 In another study, 81% of smokers with a family history of lung cancer considered or planned to quit smoking (contemplation or preparation phase), while this proportion was about 13% lower in smokers without a family history of lung cancer. 21…”
Section: Discussionmentioning
confidence: 95%
“…In theory, such communication would link the referral to patient-specific benefits rather than the generic possibility of improved function. While it is likely that such communication would increase receptivity, it is somewhat moot as reports consistently suggest that scant attention is paid to either the detection or treatment of functional limitations among cancer populations, even at National Cancer Institute-designated centers with established cancer rehabilitation programs 9,10,12,13,42 Although similar items have been validated across a range of health care services, 27,28 none have been specifically vetted to assess attitudes towards function-directed care. Nevertheless, we believe that participants’ responses are informative and accurately reflect their attitudes for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Participants were provided four response options; 1) No, 2) Yes, 3) Currently receiving rehabilitation services, and 4) Previously received rehabilitation services for current limitations.…”
Section: Methodsmentioning
confidence: 99%